2015
DOI: 10.1007/s00268-015-3230-2
|View full text |Cite
|
Sign up to set email alerts
|

Ex Vivo Intra‐arterial Methylene Blue Injection in Rectal Cancer Specimens Increases the Lymph‐Node Harvest, Especially After Preoperative Radiation

Abstract: The use of methylene blue staining of rectal carcinoma preparations leads to a significant increase in the number of lymph nodes examined after neoadjuvant RCT. This can be expected to improve the accuracy of lymph-node staging of neoadjuvant-treated rectal carcinoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
14
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 38 publications
0
14
0
Order By: Relevance
“…All previous studies assessing ex vivo intra-arterial staining in colorectal cancer have used methylene blue. [8][9][10][11][12][13][14] However, the present study indicates that IC is a possible alternative to methylene blue in advanced lymph node staging of rectal cancer. For ex vivo use, both dyes are effective and pose no risk to the patient.…”
Section: Discussionmentioning
confidence: 56%
See 4 more Smart Citations
“…All previous studies assessing ex vivo intra-arterial staining in colorectal cancer have used methylene blue. [8][9][10][11][12][13][14] However, the present study indicates that IC is a possible alternative to methylene blue in advanced lymph node staging of rectal cancer. For ex vivo use, both dyes are effective and pose no risk to the patient.…”
Section: Discussionmentioning
confidence: 56%
“…The studies assessing methylene blue injections found that staining techniques have no impact on the number of positive lymph nodes or the nodal stage. 9,12–14 Even in small lymph nodes (≤4 mm), staining techniques did not seem to increase the number of identified metastasis. 14 The results of the present study support these findings.…”
Section: Discussionmentioning
confidence: 92%
See 3 more Smart Citations